PENGARUH SISTEM PEMBINAAN, SARANA PRASARANA DAN PENDIDIKAN LATIHAN TERHADAP KOMPETENSI KINERJA GURU PENDIDIKAN JASMANI SEKOLAH DASAR DI KOTA SEMARANG - Pramono, Harry (Jurnal Penelitian Pendidikan, 2012)
Performance of teachers in teaching and learning became one of the most important part in supporting the creation of the educational process effectively, especially in building discipline and quality of student learning outcomes. Efforts to improve the professionalism of teachers should consider the improvement of education quality, teachers quality and how teachers teach is an important factor in explaining the learning outcomes of students. This study is reviewing the system of guidance, educational training, and infrastructure through pedagogic competence, personality, social and professional education on the performance of elementary school teachers using the approach path analysis. The population in this study were all physical education teachers in primary school in district of Semarang, the amount 285 persons, with minimized sample amounted to 74 people and taken propotionate using multistage random sampling. The results of this study is a variable that directly affects the competence of teachers is a system of guidance, facilities, educational training. While that directly affect the performance of teachers is the coaching system and infrastructure. Education and training are not proven to directly affect the performance of physical education teachers. System development, infrastructure, educational training directly affects the performance of physical education teachers through competence, but competence is not directly influence the performance of physical education teachers.